Active chest tube clearance after aortic valve surgery did not influence amount residual pericardial fluid after aortic valve replacement in a randomised trial. (3rd May 2020) - Malgerud, Linnéa; Maret, Eva; Reitan, Christian; Ivert, Torbjörn
Abstract: Objective. Evaluate if the use of active clearance of chest tubes after aortic valve surgery influenced bleeding and reduced postoperative residual pericardial effusion. Design. Prospective randomised trial comparing PleuraFlow ® 32 F chest tube with FlowGlide™ active clearance to a standard Argyle ® 32 F chest tube in 100 patients undergoing aortic valve surgery. Chest tube outputs and pericardial effusion measurements assessed by two-dimensional transthoracic echocardiography were recorded before hospital discharge. Results. Postoperative chest tube outputs per hour did not differ between the two groups. The median chest tube output was 400 mL for patients who had a PleuraFlow ® chest tube vs . 490 mL for patients with an Argyle ® chest tube ( p = .08). Pericardial effusions ≥ 2 mm were detected in 76% vs. 68% of the patients ( p = .50) and postoperative atrial fibrillation occurred in 42% vs . 34% ( p = .54), respectively. Conclusions. Use of active clearance chest tubes, compared to standard chest tubes after aortic valve surgery did not differ significantly regarding postoperative bleeding or degree of pericardial effusion as measured by echocardiography prior to hospital discharge.